4CPS-092 Collaborative approach to improve adherence and retention in care among illicit drug users with hiv/aids. (2nd March 2018) - Pardeiro, N Valcarce; Alvarez, H; Santalla, J; García, JF; Rodriguez, I; Mariño, A
Abstract : Background: There is a need for developing strategies to improve outcomes of antiretroviral therapy (ART) among HIV-positive drug users with poor psychosocial support. Purpose: Evaluate the results of a strategic collaboration between the Infectious Diseases Unit (IDU), Hospital Pharmacy (HP) and Drug Addiction Association (ASFEDRO) to improve ART adherence and retention in care among drug users with HIV/AIDS. Material and methods: IDU and HP identified HIV-positive drug users with unsuccessful medical appointments, irregular ART dispensing records and difficulties of compliance. The strategic collaboration intended to integrate ART in a methadone maintenance programme (MMT). Every Tuesday, an ASFEDRO pharmacist met IDU to discuss previously selected patients and collect their ART at HP. According to prescriptions, hospital pharmacists validated and dispensed ART for 1 month. Patients attended the ASFEDRO facilities where the pharmacist delivered methadone and ART over the same period of time, conducted counselling sessions to enhance drug adherence behaviour and reinforced appointment compliance with medical care. A post-implementation study was done. Variables collected were socio-demographic, clinical, ART-related and psychosocial. Adherence was evaluated through ASFEDRO records. Maintenance in HIV care was evaluated through blood tests and medical consultation appointments. Statistical analyses were done using SPSS v. 21. Results: Data were available in 40 patients (75% males, mean age 49 (39–66) years). Sixty per cent were in CDC stage C and 70% were HCV co-infected. Mean duration of HIV infection was 16 (2–31) years. 47.5% had been in prison, 60% had sporadic or frequent alcohol and/or illicit drugs consumption, 35% had psychiatric comorbidity, 62.5% had taken between 5 and 10 ART regimens and 5% more than 10. At the time of inclusion, 42.5% had detectable viral load (VL). During follow-up, 208 consultation appointments and 76 blood tests were retrieved. One patient died, two patients left MMT, two patients moved to another location and 35 patients (87.5%) continued on ART and engaged in HIV care. Adherence was 95% to 100%. VL was below 50 copies/ml in all patients and below 20 copies/ml in 95%. Conclusion: The strategic collaboration between IDU, HP and ASFEDRO linked ART with MMT, and improved adherence and maintenance in the care of HIV-positive drug users. References and/or Acknowledgements: Medication adherence strategies for drug abusers with HIV/AIDS No conflict of interest